2018
DOI: 10.1039/c8lc00250a
|View full text |Cite
|
Sign up to set email alerts
|

Continuous removal of small nonviable suspended mammalian cells and debris from bioreactors using inertial microfluidics

Abstract: Removing nonviable cells from a cell suspension is crucial in biotechnology and biomanufacturing. Labelfree microfluidic cell separation devices based on dielectrophoresis, acoustophoresis, and deterministic lateral displacement are used to remove nonviable cells. However, their volumetric throughputs and test cell concentrations are generally too low to be useful in typical bioreactors in biomanufacturing. In this study, we demonstrate the efficient removal of small (<10 μm) nonviable cells from bioreactors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 52 publications
1
41
0
Order By: Relevance
“…In this case, the concentration of the particles in different lateral positions depends on the ratio of the lift force discussed earlier, and the dean drag force created by dean flow. As a result, it will require a shorter distance to focus the current, Providing reduced hydrodynamic resistance, which is promising for focusing or separating inertia [55].…”
Section: Physics Of Secondary Flow and Applicationmentioning
confidence: 99%
“…In this case, the concentration of the particles in different lateral positions depends on the ratio of the lift force discussed earlier, and the dean drag force created by dean flow. As a result, it will require a shorter distance to focus the current, Providing reduced hydrodynamic resistance, which is promising for focusing or separating inertia [55].…”
Section: Physics Of Secondary Flow and Applicationmentioning
confidence: 99%
“…37 Current methods for separation of dead cells include inclined settlers 39 and more recently also compact settlers. 40 Kwon et al 41 applied inertial microfluidics to separation of nonviable cells and cell debris from viable CHO cells. CHO cells are the most frequently used hosts for expression of recombinant proteins, accounting for more than 70% of the total worldwide recombinant proteins.…”
Section: B Separation Of Live and Dead Cellsmentioning
confidence: 99%
“…Separation of the generally smaller dead cells in inertial microfluidic systems is difficult, because viable and nonviable cells overlap partly in size which sets a natural limit for the efficiency of the separation process. 41 The size difference is caused by cell-shrinkage in the early stages of apoptosis which is important for regulating the activity of apoptotic nucleases and caspases. 42 In their experiments 41 , Kwon and co-workers focused on maintaining high viable cell…”
Section: B Separation Of Live and Dead Cellsmentioning
confidence: 99%
“…Various alternatives to FACS and MACS for cellular therapies, such as mRBC production, have been proposed and were recently reviewed (Masri, Hoeve, Sousa, & Willoughby, 2017). Recent work on deterministic lateral displacement (Campos‐Gonzalez et al, 2018) and inertial vortexes (Pritchard et al, 2019) have demonstrated application to CAR‐T cell processing and inertial focussing has been used to isolate, enrich, and purify stem cells (Hur, Brinckerhoff, Walthers, Dunn, & Di Carlo, 2012; Lee et al, 2018; Song et al, 2017), to obtain desired subpopulation (Lee et al, 2011, 2014; Poon et al, 2015), to isolate single cells from clusters (Nathamgari et al, 2015), for nonviable cell removal (Kwon, Yao, Hamel, & Han, 2018) as well as microcarrier scaffold removal (Moloudi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%